Left ventricular diastolic dysfunction worsens prognosis in patients with heart failure due to dilated cardiomyopathy - Winiarczyk, Mateusz; Dziewięcka, Ewa; Wiśniowska‐Śmiałek, Sylwia; Stępień, Agnieszka; Graczyk, Katarzyna; Leśniak‐Sobelga, Agata; Hlawaty, Marta; Woźniak, Jakub; Savitskaya, Maryia; Holcman, Katarzyna; Kostkiewicz, Magdalena; Podolec, Piotr; et al. (ESC Heart Failure, 2025)
Aims The prognostic significance of left ventricular (LV) diastolic dysfunction (LVDD) severity in patients with dilated cardiomyopathy (DCM) remains uncertain. This study aimed to evaluate the association of LVDD severity and elevated left atrial pressure (eLAP) with patient outcomes in stable, non‐acutely decompensated patients with DCM. Methods This single‐centre, retrospective, observational study involved 740 DCM patients (either inpatients or outpatients) managed at our tertiary cardiac centre between 2010 and 2021. Due to incomplete data, 96 patients were excluded. LVDD and eLAP were assessed using echocardiography according to the 2016 guidelines of the European Association of Cardiovascular Imaging (EACVI). The primary outcomes were all‐cause mortality and heart failure (HF)‐related mortality. Results The final cohort comprised of 644 DCM patients [mean age: 52 ± 12 years, LV ejection fraction (LVEF): 26 ± 10%]. Over a median follow‐up period of 41 (18.5–66.7) months, 105 (16.3%) patients died: 8 (5.3%) patients in the normal left atrial pressure (nLAP) group and 97 (19.6%) patients in the eLAP group. eLAP was identified as an independent prognostic factor for both all‐cause mortality [hazard ratio (HR) 2.0; 95% confidence interval (CI) 1.1–3.7; P = 0.01] and HF‐related mortality (HR 2.5; 95% CI 1.01–6.5; P = 0.04), even after adjusting for LVEF and atrial fibrillation (AF) presence. Additionally, HF‐related mortality rates were significantly higher in patients with moderate to severe LVDD compared with those with mild LVDD [5 (3.3%) vs. 67 (13.6%), P < 0.05]. Conclusions This study's findings highlight the importance of assessing the severity of LVDD in patients with DCM, which provides incremental prognostic information over LVEF.